2000
DOI: 10.1007/s11926-000-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Pain in patients with fibromyalgia syndrome

Abstract: Chronic diffuse pain and hyperalgesia are two cardinal features of pain in fibromyalgia syndrome (FMS). Advancement in understanding the pathophysiology and treatment efficacy often depends on pain that is defined and measured. Pain is a subjective phenomenon that we can measure only by indirect methods. In this article, we provide methodological guidelines for pain assessment and review recent developments in understanding pain mechanisms and evaluating treatments in FMS. Finally, we demonstrate the heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Despite efforts to objectively evaluate pain, it continues to remain a uniquely personal experience [25]. It is a challenging task for physicians serving patients with chronic pain to accurately assess the intensity, duration and nature of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to objectively evaluate pain, it continues to remain a uniquely personal experience [25]. It is a challenging task for physicians serving patients with chronic pain to accurately assess the intensity, duration and nature of pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies do not offer evidence in favor of cognitive-behavioral therapy over group programs of education and exercise (82). It has been suggested that cognitive-behavioral therapy may be especially effective in patients who are characterized by a high level of pain, reduced quality of life, emotional distress, lack of control over their lives, and functional limitations (83,84).…”
Section: Cognitive-behavioral Interventionsmentioning
confidence: 99%
“…Despite efforts to objectively evaluate pain, it continues to remain a uniquely personal experience [4,5]. It is essential for physicians serving patients with chronic pain to accurately assess the intensity, duration and nature of pain in order to determine whether new treatment modalities are deemed to be effective or not [5].…”
Section: Assessment Of Painmentioning
confidence: 99%
“…The diverse symptoms, poorly understood etiology and pathophysiology make FM a frustrating condition for patients and physicians [1,2]. The complexity or heterogeneity of the condition requires individualised evaluation and multidisciplinary approach to the treatment [1,[3][4][5]. The complexity or heterogeneity of the condition requires individualised evaluation and multidisciplinary approach to the treatment [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation